Blacks And Blues: The Imaginative Territory Of Gayl Jones (International Journal of Environmental Sciences, 2025)
Gayl Jones has intense fascination for the blues. She wrote her two novels Corregidora (1975) and Eva’s Man (1976) as blues narratives. These two novels won her instant fame and she is now highly regarded as the innovative voice of Afro-American women. After a twenty year break, Jones published two additional novels, The Healing (1998) and Mosquito (1999). Jones is also known for her short-stories and poetry.In her first person narratives, Jones describes the sexual and racial violence imposed on Black women, highlighting these women’s various responses to their suffering. She is celebrated as one of the earlier writers to focus extensively on sexual violence and its relationship to Black women. Jones’ clear focus on feminism over racism and the brutal nature of her subject matter have sparked negative responses in some evaluations, but she has earned the praise of fellow writers such as Toni Morrison, James Baldwin, and John Updike.